KEANEKARAGAMAN VEGETASI PADA SISTEM AGROFORESTRI DUKUH DI DESA BIIH KABUPATEN BANJAR KALIMANTAN SELATAN - Davita, Almira; Kissinger, Kissinger; Syam'ani, Syam'ani (Universitas Lambung Mangkurat, 2024)
In order to support the development and management of agroforestry in the hamlet, it is necessary to understand the ecological conditions and vegetation structure through this research. The objective of this study is to analyze the dominance, species diversity, and evenness of vegetation in the agroforestry system of the hamlet in Biih Village. Data collection was conducted using vegetation analysis techniques with a combination of transect and plot methods, employing purposive sampling along transects in agroforestry areas located behind or adjacent to residential areas. Vegetation data were analyzed using the Importance Value Index, Species Diversity Index, and Species Evenness Index. The research findings reveal that the plant species composition in the agroforestry system of the hamlet consists of 27 species from 19 families, with a total of 671 individuals. The dominant species include Teratat, Porang, Pepper, and Lombok at the understory level, Rubber, Coffee, and Jengkol at the seedling stage, Rubber, Langsat, and Cempedak at the pole stage, Langsat, Rubber, Sungkai, and Gamal at the pole stage, and Durian, Cempedak, Rubber, and Langsat at the tree stage. The species diversity and evenness at all growth stages are classified as moderate, indicating a relatively stable ecosystem, with high evenness or nearly equal distribution.Guna mendukung pengembangan dan pengelolaan agroforestri dukuh perlu diketahui kondisi ekologi dan struktur vegetasi melalui penelitian ini. Tujuan dari penelitian ini adalah untuk menganalisis dominansi, keanekaragaman dan kemerataan jenis vegetasi agroforestri dukuh di Desa Biih. Pengambilan data menggunakan teknik analisis vegetasi dengan metode kombinasi jalur berpetak dengan penempatan jalur secara purposive sampling dan lahan agroforestri dukuh yang menjadi objek penelitian dibelakang atau berdekatan dengan kawasan pemukiman. Data vegetasi dianalisis menggunakan Indeks Nilai Penting, Indeks Keanekaragaman Jenis dan Indeks Kemerataan Jenis. Hasil penelitian menunjukkan komposisi jenis tumbuhan yang ditemukan pada kawasan agroforestri dukuh terdiri dari 27 jenis, 19 famili dan 671 individu yang didominasi oleh jenis teratat, porang, lada dan Lombok pada tumbuhan bawah, jenis karet, kopi dan jengkol pada tingkat semai, jenis karet, langsat dan cempedak pada tingkat pancang, jenis langsat, karet, sungkai dan gamal pada tingkat tiang dan jenis durian, cempedak, karet dan langsat pada tingkat pohon. Indeks keanekaragaman dan kemerataan pada semua tingkat pertumbuhan tergolong kedalam tingkat keanekaragaman jenis sedang atau ekosistem yang stabil dengan kemerataan tergolong tinggi atau hampir merata penyebarannya.